Business schools in transition? Issues of impact, legitimacy, capabilities and re-invention - THOMAS, Howard (Institutional Knowledge at Singapore Management University, 2012)
The purpose of this editorial is to introduce the set of papers which comprise this issue of the journal, and to provide an interpretation of the current strategic debates about the future evolution of business school paradigms and, hence, identify possible strategic options. The papers can be categorized into three broad themes: first, the impacts and environmental influences on management education including issues of globalization, global sustainability and advances in digital and social media. Second, challenges and criticisms of management education covering issues of legitimacy, business model sustainability and the need for change in business models. Third, the re-invention of business schools and the creation of alternative models of management education and approaches for effective implementation and delivery of those models. Findings – Globalization is an important environmental influence. Arnoud de Meyer, the President of SMU, offers his reflections. The paper by Peter Lacy and his colleagues at Accenture builds on the theme of globalization by examining the new era of global sustainability in the management arena. In discussing the second theme of challenges and criticisms, David Wilson and Howard Thomas examine the continued legitimacy of the business school with respect to both academic legitimacy in the university and business relevance and thought leadership legitimacy in the management community. Kai Peters and Howard Thomas address the issue of the sustainability of the current business school financial model and question whether it is too luxurious. Santiago Iñiguez and Salvador Carmona reinforce this urgent need to review the sustainability and viability of the existing business school models. Building on the importance of technology impacts, James Fleck illustrates how the Open University Business School (OUBS), the leader and pioneer in blended and distance learning in management education, has focused on further developing models of blended learning which will challenge the current weak adoption of such models in well-known business schools. Rich Lyons, on the other hand, presents a thoughtful analysis of the careful implementation of a completely new MBA curriculum at the well-regarded Haas Business School at Berkeley. Peter Lorange's “network-based” model, on the other hand, is the most radical change model. Granit Almog-Bareket's leadership paper offers one perspective on the importance of business school leadership in creating the conditions for innovative and insightful management of business school futures. Clearly, debates and criticisms of business schools will continue to be addressed. It is a sign of a healthy academic and management community that such debates – particularly through the auspices of EMFD – can be presented in an open and constructive manner, as in this special issue of the Journal of Management Development.